Counseling practices of therapists in the promotion of exercise and nutrition behaviors in therapy: a qualitative study - Millard, Lauren, author; Rickard, Kathryn, advisor; Banning, James, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2013)
With the growing amount of evidence supporting the benefits of exercise and nutrition for mental health and psychological well-being, it is interesting to note that mental health professionals may have a tendency not to recommend them to clients in therapy. The purpose of the present study was to examine the current practices of professional psychologists, specifically clinical and counseling psychologists, with regard to whether and how often they suggest exercise and nutrition to clients, what therapeutic methods or techniques they might use, and how much and what type of training and education they perceive may be necessary for psychologists to address these issues in therapy. Participants were 17 licensed clinical and counseling psychologists holding either a master's or doctoral degree in psychology. They took part in individual, face to face, semi-structured interviews regarding their practices in discussing nutrition and exercise in therapy. Data were analyzed using post-positivist grounded theory and constant comparative analysis. Results produced themes that fell into one of four categories: Therapist Attributes, Client Attributes, Counseling Methods, and Therapist Health. A theoretical model was developed to describe if and how the therapist attributes and the client attributes related. This relationship influenced how participants would address nutrition and exercise in therapy. Various therapeutic approaches included inquiring about the client's current practices, providing psychoeducation, making clear recommendations, collaborating with the client and other professionals, and making appropriate referrals.
Keywords: counseling; therapy; nutrition; exercise